Clinical Impact of Intravascular Ultrasound Guidance During Endovascular Treatment of Subclavian Artery Disease. (October 2017) - Chung, Wen-Jung; Soga, Yoshimitsu; Tomoi, Yusuke; Fujihara, Masahiko; Okazaki, Shinya; Yamauchi, Yasutaka; Shintani, Yoshiaki; Suzuki, Kenji
Purpose: To evaluate the short- and long-term efficacy of intravascular ultrasound (IVUS) guidance during endovascular treatment (EVT) of subclavian artery disease.Methods: The multicenter SCALLOP registry (SubClavian Artery disease treated with endovascuLar therapy; muLticenter retrOsPective registry) was interrogated to identify 542 patients who underwent successful EVT for SCAD between January 2003 and December 2012. Lesions were classified according to the use of IVUS guidance: 177 patients (mean age 68.9±8.6 years; 149 men) with and 373 patients (mean age 69.9±8.7 years; 275 men) without. The main outcome was the difference in primary patency; secondary outcomes were differences in assisted primary patency, secondary patency, overall survival, freedom from major adverse cardiovascular events [MACE; all-cause mortality, myocardial infarction (MI), and stroke], and freedom from major adverse events (MAE). Multivariate analysis of the IVUS+ group was performed to identify predictors of failure; results are presented as the hazard ratio (HR) and 95% confidence interval (CI).Results: In total, 538 (97.8%) lesions were treated with stents and 12 lesions by balloon angioplasty alone. Periprocedural and in-hospital overall complication rates did not differ significantly between IVUS+ (10.2%) and IVUS– (8.8%, p=0.617). Long-term follow-up demonstrated no significant difference between IVUS+ and IVUS– groups in 5-year all-cause mortality (p=0.37), MI (p=0.07), stroke (p=0.31), or MACE (p=0.07). However, 5-year primary patency was significantly higher in the IVUS+ group (88.5% vs 77.7%, p=0.03). There were no group differences in 5-year assisted primary patency (90.4% vs 89.9%, p=0.81) or secondary patency (99.4% vs 97.1%, p=0.25). Multivariate analysis of the IVUS+ group identified in-hospital stroke (HR 16.92, 95% CI 3.60 to 79.42, p<0.01) and combined use of balloon-expandable and self-expanding stents (HR 5.59, 95% CI 1.22 to 25.65, p=0.02) as independent negative predictors of primary patency.Conclusion: These results suggest that IVUS guidance can significantly improve long-term primary patency following endovascular treatment of subclavian artery disease.